Peran Ustadz Dalam Mengatasi Problematika Santri Di Pondok Modern Darussalam Gontor Kampus 10 Jambi - Hamdani Saputra (Universitas Yudharta Pasuruan, 2021)
This study aims to find out about the role of the ustadz at Pondok Moderi Darussalam Gontor Campus 10 Jambi in dealing with the problems of students, to find out what the problems of students are going on, and what the teacher will do to change the students for the better. The method in this study uses a qualitative approach, as the research subjects are the director of KMI, KMI teacher and students, the location of this research is in the modern boarding school Darussalam gontor campus 10 jambi. The results of the study show that the role of the teacher in dealing with students at the Darussalam Gontor modern boarding school, campus 10 Jambi is to carry out a good role, as for the problems of students in the Darusslam Gontor modern boarding school, campus 10 Jambi, there must be the number of students who violate the rules and discipline of the Islamic boarding school, and as for overcoming the problems of students. This can be done in a way that the ustadz must be disciplined and give correct and good examples and always provide an understanding of the students.